Validation of the names Piper sugandhi and Piper sugandhi var. brevipilis (Piperaceae) - Sarnaglia Junior, Valderes Bento; Freitas, Joelcio; de Lirio, Elton John (Phytotaxa, 2016)
Piper Linnaeus (1753:28) is a Pantropical genus that comprises about 2000 species (Quijano-Abril et al. 2006). This genus is economically important because is widely used as spice, as P. nigrum Linnaeus (1753:28) (black pepper) and as a medicinal plant across the world. Babu et al. (1993) described a new species and a variety to the genus from Southern India: Piper sugandhi Ravindran, Babu & Naik (1993:27) and P. sugandhi var. brevipilis Ravindran, Babu & Naik (1993:27). The authors provided diagnosis for the new species and variety, and compared it with the related taxa. However, they have indicated two gatherings as holotypes (a male and a female specimen) and according to Arts. 8.1 and 40.1 of the ICN these two names are not validly published (McNeill et al. 2012).